Construction of analogs of the Lyapunov equation for a matrix polynomial - Mazko, A. G. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We develop a method for localization of the eigenvalues of a matrix polynomial. This method is related to a generalization and solution of the Lyapunov equation.